Expanding the allergen repertoire of salmon and catfish. Issue 5 (15th October 2020) - Ruethers, Thimo; Taki, Aya C.; Karnaneedi, Shaymaviswanathan; Nie, Shuai; Kalic, Tanja; Dai, Danyi; Daduang, Sakda; Leeming, Michael; Williamson, Nicholas A.; Breiteneder, Heimo; Mehr, Sam S.; Kamath, Sandip D.; et al.
Abstract: Background: Diagnostic tests for fish allergy are hampered by the large number of under‐investigated fish species. Four salmon allergens are well‐characterized and registered with the WHO/IUIS while no catfish allergens have been described so far. In 2008, freshwater‐cultured catfish production surpassed that of salmon, the globally most‐cultured marine species. We aimed to identify, quantify, and compare all IgE‐binding proteins in salmon and catfish. Methods: Seventy‐seven pediatric patients with clinically confirmed fish allergy underwent skin prick tests to salmon and catfish. The allergen repertoire of raw and heated protein extracts was evaluated by immunoblotting using five allergen‐specific antibodies and patients' serum followed by mass spectrometric analyses. Results: Raw and heated extracts from catfish displayed a higher frequency of IgE‐binding compared to those from salmon (77% vs 70% and 64% vs 53%, respectively). The major fish allergen parvalbumin demonstrated the highest IgE‐binding capacity (10%‐49%), followed by triosephosphate isomerase (TPI; 19%‐34%) in raw and tropomyosin (6%‐32%) in heated extracts. Six previously unidentified fish allergens, including TPI, were registered with the WHO/IUIS. Creatine kinase from salmon and catfish was detected by IgE from 14% and 10% of patients, respectively. Catfish L‐lactate dehydrogenase, glyceraldehyde‐3‐phosphate dehydrogenase, pyruvate kinase, and glucose‐6‐phosphate isomerase showed IgE‐binding for 6%‐13% of patients. In salmon, these proteins could not be separated successfully. Conclusions: We detail the allergen repertoire of two highly farmed fish species. IgE‐binding to fish tropomyosins and TPIs was demonstrated for the first time in a large patient cohort. Tropomyosins, in addition to parvalbumins, should be considered for urgently needed improved fish allergy diagnostics. Abstract : Catfish raw and heated extracts demonstrate higher prevalence and diversity of IgE‐binding as compared to salmon. PV, TM and TPI are the most prominent IgE‐binding fish proteins, followed by Eno, Ald and GAPDH. TM is the second most abundant protein, after PV, in heated extracts and up to 49% of 77 fish‐allergic children demonstrate IgE‐binding. Abbreviations: Ald, aldolase; Eno, enolase; GAPDH, glyceraldehyde‐3‐phosphate dehydrogenase; MS, mass spectrometry, PV, parvalbumin, SDS‐PAGE, sodium dodecyl sulphate‐polyacrylamide gel electrophoresis; TM, tropomyosin, TPI, triosephosphate isomerase